(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
This article discusses the meaningfulness of a word in context, alternative sounds in speech and semantic differences. The article deals with synonymic and homonymic issues in lexical and semantic terms. Natural combination of sounds as the basis of the system in Kyrgyz language.